Energy and centrality dependence of anti-p and p production and the anti-Lambda/anti-p ratio in Pb+Pb collisions between 20A GeV and 158A GeV - Alt, C. (Array, 2006)
The transverse mass mt distributions for antiprotons are measured at midrapidity for minimum bias Pb+Pb collisions at 158A GeV and for central Pb+Pb collisions at 20A, 30A, 40A, and 80A GeV beam energies in the fixed target experiment NA49 at the CERN SPS. The rapidity density dn/dy, inverse slope parameter T, and mean transverse mass <mt> derived from the mt distributions are studied as a function of the incident energy and the collision centrality and compared to the relevant data on proton production. The shapes of the mt distributions of anti-p and p are very similar. The ratios of the particle yields, anti-p/p and anti-Lambda/anti-p, are also analyzed. The anti-p/p ratio exhibits an increase with decreasing centrality and a steep rise with increasing beam energy. The anti-Lambda/anti-p ratio increases beyond unity with decreasing beam energy.